Underwater acoustic localisation and referencing: an enhanced subsurface positioning method for archaeological data collection of submerged cultural resources - Thompson, MH (2023)
Traditional and modern optical methods of maritime archaeological site documentation typically lack absolute spatial information as part of submerged cultural heritage surveys in locations where shore-based satellite positioning technologies are not applicable for use. This is due to the inability to use satellite positioning receivers beneath the water surface as a result of the high attenuation rate of electromagnetic waves in a marine environment. The defence and offshore energy industries solved this problem through the incorporation of acoustic ranging systems used in conjunction with satellite positioning receivers. Underwater acoustic ranging equipment, such as ultra-short baseline (USBL) and long baseline (LBL) systems, are commonly used in geophysical surveys and marine construction projects to provide subsurface positioning information of underwater instrumentation such as towed sonar arrays, remotely-operated vehicles (ROVs), and divers. Satellite positioning and underwater acoustic ranging configurations have been in continuous use for more than three decades, and such equipment systems are readily available throughout the world for commercial and scientific applications. Despite the proven effectiveness and accessibility of these systems, maritime archaeology fieldwork practices have not successfully integrated these systems into established underwater data collection techniques. This thesis was established to determine if traditional and modern optical maritime archaeological data collection techniques are capable of being supplemented by a tandem satellite positioning system and USBL acoustic ranging configuration to provide underwater positioning information in accordance with universally-accepted geophysical surveying spatial and equipment standards, such as those published by the International Hydrographic Organization (IHO), Bureau of Ocean Energy Management (BOEM), Historic England, and others. In the absence of recognised spatial standards within the maritime archaeology community, this thesis relied on geophysical surveying spatial and equipment standards as the research parameters upon which the Underwater Acoustic Localisation and Referencing (UALR) methodology was developed. The UALR methodology presented in this thesis successfully incorporated a GPS/USBL configuration for providing subsurface latitude and longitude coordinates for ground control point positions for traditional and modern optical archaeological data collection techniques. The collected datasets were georeferenced using underwater spatial information gathered by the UALR methodology process, and demonstrated that these methods are capable of achieving spatial accuracy and measurement precision in accordance with geophysical surveying specifications. By adhering to these standards, the UALR methodology is applicable for use by archaeologists in support of geophysical surveying operations throughout the world.